Корелација на класичните хистоморфолошки параметри со параметрите од молекуларната класификација на карцином на дојка - Јашар, Џенгис (Медицински факултет, УКИМ, Скопје, 2016)
OBJECTIVE: Breast cancer (BC) is the most commonly diagnosed cancer in women worldwide characterized by molecular and clinical heterogeneity that results with multiple intrinsic tumor subtypes. The aim of this study was to evaluate the occurrence of relapses in the different immunophenotypes of BC associated with different histological parameters. METHODS: The retrospective population study included 192 BC patients diagnosed between 2007 and 2010 in our hospital. Molecular subtype classification was performed on immunohistochemical surrogates for estrogen (ER) and progesterone receptor (PR), as well as for proliferation index (Ki-67) and Human Epidermal Growth Factor receptor-2 (HER-2), according to St. Gallen International Expert Consensus recommendations from 2013. During the follow-up period (min.12,2, max. 75,3, mean 46,6+16,6 months), that includes 173 patients, recurrences were observed in 35 patients (20,2%). BC immunophenotypes and histomorphological/clinical parameters were analyzed in terms of disease free survival (DFS) in a multivariate fashion using a Cox regression model. RESULTS: Proportions of BC immunophenotypes were: Luminal A-26,56%; Luminal B-41.67%; HER2+ 18,75% and Triple-negative-13,02%. In the Univariate analyses there was a significant difference in the distribution of age, tumor diameter, mitotic index, lympho-nodal ratio, Nottingham Prognostic Index (NPI), stage of the disease, Ki67 PI and the bcl-2 overexpression among the four BC immunophenotypes. In the multivariate analyses, the age, tumor diameter and the stage of the disease were represented as independent prognostic factors of recurrent disease in different BC immunophenotypes. CONCLUSION: The prognostic value of BC immunophenotypes persists when adjusting the age, the tumor diameter and the stage of the disease and this “morphologic-molecular” model was robust in relapse prediction and recurrence risk stratified by traditional prognostic parameters.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Гордана Петрушевска.
Keywords: breast cancer, immunophenotypes, molecular classification, relapses